Prognostic Insights in Feline Mammary Carcinomas: Clinicopathological Factors and the Proposal of a New Staging System - Mónica Monteiro; Gonçalo Petrucci; Felisbina L. Queiroga (Animals)
Feline mammary carcinoma (FMC) is an aggressive neoplasm with a poor prognosis. Clinical staging is crucial for risk assessment, yet the current WHO system lacks granularity, particularly in Stage III. Aligning this system with human breast cancer staging has the potential to improve prognostic accuracy. Additionally, prognostic factors such as tumor size, ulceration, lymph node metastasis, and lymphovascular invasion require further evaluation. This study retrospectively analyzed 75 female cats with FMC to assess the prognostic impact of clinicopathological factors and evaluate a novel staging system (new staging) adapted from the AJCC Cancer Staging Manual. Survival analyses included disease-free interval (DFI), and overall survival (OS). Tumor size >3 cm (p < 0.001), ulceration (p = 0.010), lymphovascular invasion (p < 0.001), lymph node metastasis (p < 0.001), WHO and new staging (p < 0.001) were significantly associated with shorter survival. The new staging refined Stage III into IIIA (T3N0M0), IIIB (T4N0M0), and IIIC (AnyTN1M0), improved prognostic differentiation. Stage IIIC cases had the worst survival (p < 0.001). Multivariate survival analysis identified lymphovascular invasion (HR = 2.834, 95% CI: 1.546–5.195, p = 0.001), histological Grade II (HR = 5.013, 95% CI: 1.122–22.397, p = 0.035) and III (HR = 9.894, 95% CI: 2.195–44.594, p = 0.003) and skin ulceration (HR = 2.462, 95% CI: 1.256–4.825, p = 0.009). These findings support the prognostic relevance of key clinicopathological factors in FMC and highlight the advantages of a refined TNM-based staging system, which may enhance risk stratification and therapeutic decision-making in veterinary oncology.